On the predictive validity of the National Football League combine: does it forecast future success? - Rishis, E.; Johnston, K.; Baker, J. (Journal of Sports Sciences, 2023)
The National Football League (NFL) Combine provides NFL teams the ability to assess prospective athletes` medical histories and physical and psychological abilities. Using this information, NFL personnel must then decide whether an athlete is a good fit to their team. Given the combine`s 40-year history and the availability of peer reviewed articles on the function and efficacy of the combine, the purpose of this systematic review was to synthesize the literature evaluating the predictive validity of the combine according to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). Full-text, peer-reviewed articles containing information relevant to the NFL combine and at least one measure of future success were retained. The search yielded 1954 articles and after screening, 68 articles remained. These remaining articles focused on measures of success pertaining to (a) medical testing and future performance (n = 25), (b) combine tests (n = 12), (c) draft position (n = 10), (d) draft and future performance (n = 8), (e) medical testing (n = 7), (f) career longevity (n = 3), (g) draft and salary (n = 2), and (h) playing performance (n = 1). Due to the mixed results of combine measures on future success, this review highlights the need for more research to investigate the combine`s influence on long-term performance and success.